BLOOD BIOMARKERS TO PREDICT OF THE ONSET AND ADVERSE OUTCOMES OF PREECLAMPSIA : A SYSTEMATIC REVIEW - Aldela Paramerta, I Made Elga (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Pre-eclampsia is one of the most common pregnancy complications, and a major cause of fetal and maternal morbidity and mortality globally. Diagnosis currently takes place in the third trimester based on clinical symptoms. This systematic review sought to determine the blood biomarkers that are associated with pre-eclampsia, and in particular, the biomarkers that could predict pre-eclampsia in early pregnancy. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 257 articles, whereas the results of our search on SagePub brought up 78 articles. The results of the search conducted for the last year of 2013 yielded a total 198 articles for PubMed and 54 articles for SagePub. In the end, we compiled a total of 5 papers, 4 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria. Conclusion: PlGF and sFlt-1 are the most used in clinical practice, even if their specificity and sensitivity do not justify a default implementation into guidelines to screen all pregnant women. Their role is limited to rule-out a diagnosis of pre-eclampsia in women presenting with symptoms highly suggestive of the disease. Therefore, their current application is not useful for an early prediction of pre-eclampsia. Novel lines of research are needed to identify molecules able to detect pre-eclampsia in a timely manner and which have a predictive value high enough to justify the costs associated with routine measurements in the general pregnant population.